Descriptive analysis on students assessing the most difficult subjects in school - Al-saaidi, Salima Hamed Salim; Vankudre, Gopi Suresh; Ibrahim, Musthafa (Edelweiss Applied Science and Technology, 2025)
This study investigates the challenges students face in learning certain subjects and the underlying causes of these difficulties. A survey of 50 high school students identified three major factors: the nature of the subject, teaching methods, and curriculum design. Topics lacking practical examples and an overemphasis on theory were primary sources of misunderstanding. Students also reported challenges with problem-solving and asking questions in class. These findings highlight the need for interventions and teaching strategies to address these issues, fostering better understanding and improving learning outcomes.